Feasibility and acceptability of a community health worker administered behavioral activation intervention for postpartum depression: a single arm pilot study from India - Szajna, Amy; Tekkalaki, Bheemsain; Nandagaon, Veereshkumar; Udapi, Gururaj; Sogalad, Manjunath; Dandagi, Shweta; Kole, Uma; Patil, Sushma; Raddi, Sudha; Short, Vanessa; Kelly, Patricia J. (Frontiers in Psychiatry, 2024)
Introduction: Women in India experience high rates of postpartum depression (PPD), with minimal availability of screening or treatment. India has an extensive network of community health workers, known as Accredited Social Health Activists (ASHAs). While knowledgeable about most maternal-child health problems, they have minimal knowledge about PPD. We trained ASHAs to deliver a simple home-based intervention, behavioral activation (BA), which involves individuals in activities that are sources of positive reinforcement to counter depression. The research questions guiding this study were: 1) What is the feasibility and acceptability of ASHAs screening for and delivering a brief behavioral activation intervention addressing PPD among women in Belagavi, South India? 2) What impact did the brief behavioral activation intervention have on PPD? Methods: The mixed methods evaluation used interviews with participants and interventionists, and depression scores assessed pre and post. After a two-day training with 17 ASHAs that focused on understanding PPD, screening using the Edinburgh Postnatal Depression Scale (EPDS), and implementing the BA protocol, ASHAs and researcher supervisors screened mother’s 6-12 weeks postpartum presenting at pediatric immunization clinics. Mothers screening positive were invited to participate in an ASHA-led five-week BA intervention, with ASHAs visiting the mother’s homes. We conducted post-intervention EPDS scores, satisfaction assessments, and individual interviews. Results: All 26 women screening positive on the EPDS agreed to study enrollment. All participants had significant reduction (p<0.001) in PPD scores. Both ASHAs and mothers had high enthusiasm for the intervention methods and activities. Discussion: This ASHA-delivered BA intervention was found to be feasible, acceptable and effective in treating PPD in rural Indian mothers. This corroborates literature that demonstrates efficacy of a BA intervention among individuals with generalized depression in South Asia. In communities with minimal mental health resources, interventions led by trained community workers have potential for addressing PPD.